Modeling and Simulation of Wave Gait of a Hexapod Walking Robot: A CAD/CAE Approach - Abhijit Mahapatra; Shibendu Shekhar Roy; Dilip Kumar Pratihar (Institute of Advanced Engineering and Science, 2013)
In the present paper, an attempt has been made to carry out dynamic analysis of a hexapod robot using the concept of multibody dynamics. A CAD (Computer Aided Design) model of a realistic hexapod robot has been made for dynamic simulation of its locomotion using ADAMS (Automatic Dynamic Analysis of Mechanical Systems) multibody dynamics solver. The kinematic model of each leg of three degrees of freedom has been designed using CATIA (Computer Aided Three Dimensional Interactive Application) and SimDesigner package in order to develop an overall kinematic model of the robot, when it follows a straight path. Joint Torque variation as well as the variation of the aggregate center of mass of the robot was analyzed for the wave tetrapod gait. The simulation results provide the basis for developing the control algorithm as well as an intelligent decision making for the robot while in motion.